Development and external validation of a risk calculator to predict internalising symptoms among Ugandan youths affected by HIV. (August 2021) - Brathwaite, Rachel; Ssewamala, Fred M.; Neilands, Torsten B.; Nabunya, Proscovia; Byansi, William; Damulira, Christopher
Highlights: Model predicted internalizing symptoms among Ugandan AIDS-orphaned adolescents reasonably well. External validation in sample of Ugandan adolescents living with AIDS was also acceptable Models were well-calibrated confirming that predicted probabilities matched actual events. Discrimination was comparable to other psychiatric models. Abstract: The aim of the study was to develop and externally validate a model to predict individualized risk of internalizing symptoms among AIDS-affected youths in low-resource settings in sub-Saharan Africa. Longitudinal data from 558 Ugandan adolescents orphaned by AIDS was used to develop our predictive model. Least Absolute Shrinkage and Selection Operator logistic regression was used to select the best subset of predictors using 10-fold cross-validation. External validation of the final model was conducted in a sample of 372 adolescents living with HIV in Uganda. Best predictors for internalizing symptoms were gender, family cohesion, social support, asset ownership, recent sexually transmitted infection (STI) diagnosis, physical health self-rating, and previous poor mental health; area under the curve (AUC)  = 72.2; 95% CI  = 67.9-76.5. For adolescents without history of internalizing symptoms, the AUC = 69.0, 95% CI = 63.4-74.6, and was best predicted by gender, drug use, social support, asset ownership, recent STI diagnosis, and physical health self-rating. Both models were well calibrated. External validation in adolescents living with HIV sample was similar, AUC = 69.7; 95% CI = 64.1-75.2. The model predicted internalizing symptoms among African AIDS-affected youth reasonably well and showed good generalizability. The model offers opportunities for the design of public health interventions addressing poor mental health among youth affected by HIV/AIDS.